2014
DOI: 10.5194/cp-10-63-2014
|View full text |Cite
|
Sign up to set email alerts
|

Hindcasting the continuum of Dansgaard–Oeschger variability: mechanisms, patterns and timing

Abstract: Abstract. Millennial-scale variability associated with Dansgaard-Oeschger events is arguably one of the most puzzling climate phenomena ever discovered in paleoclimate archives. Here, we set out to elucidate the underlying dynamics by conducting a transient global hindcast simulation with a 3-D intermediate complexity earth system model covering the period 50 to 30 ka BP. The model is forced by time-varying external boundary conditions (greenhouse gases, orbital forcing, and ice-sheet orography and albedo) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 82 publications
9
129
1
4
Order By: Relevance
“…Depending on the background state of the climate (glacial or interglacial, orbital context …), of the simulated Atlantic Meridional Oceanic Circulation (AMOC), and the magnitude of the freshwater forcing, these models can produce a complete shutdown of the AMOC (Heinrich-like state) or a reduction of the strength of the AMOC (GS-like state) (e.g. Menviel et al, 2014). In all models, the injection of freshwater robustly produces a significant cooling of the North Atlantic region.…”
Section: Causes and Mechanisms Of The Bipolar Seesawmentioning
confidence: 99%
“…Depending on the background state of the climate (glacial or interglacial, orbital context …), of the simulated Atlantic Meridional Oceanic Circulation (AMOC), and the magnitude of the freshwater forcing, these models can produce a complete shutdown of the AMOC (Heinrich-like state) or a reduction of the strength of the AMOC (GS-like state) (e.g. Menviel et al, 2014). In all models, the injection of freshwater robustly produces a significant cooling of the North Atlantic region.…”
Section: Causes and Mechanisms Of The Bipolar Seesawmentioning
confidence: 99%
“…Extratropical heating anomalies in particular, even when zonally bound (Kang et al 2014), are found to be able to impact the ITCZ position globally, with the ITCZ shifting away from the cooling hemisphere (Broccoli et al 2006;Kang et al 2008Kang et al , 2009Chiang and Friedman 2012;Donohoe et al 2013;Schneider et al 2014). Evidence for a highlatitude forcing of tropical climate comes from numerous modeling and observational studies which suggest that changes in land and sea ice cover, AMOC strength and meltwater pulses all can impact the meridional position of the ITCZ (Chiang et al 2003;Chiang and Bitz 2005;Timmermann et al 2007;Deplazes et al 2013;Fučkar et al 2013;Marzin et al 2013;Marshall et al 2014;Menviel et al 2014;Deser et al 2015). Especially sea ice cover is known to be strongly rectified by precessional forcing (Tuenter et al 2005).…”
Section: •-mentioning
confidence: 99%
“…Seasonally the Atlantic ITCZ migrates from a position close to the equator in boreal spring to a maximum northward position around 10°N in late summer (e.g Mitchell and Wallace 1992). This seasonal march of the ITCZ has been found to be sensitive to remote climate forcing on various timescales, such as the El Niño-Southern Oscillation (Chiang et al 2002), the North Atlantic Oscillation (Marshall et al 2001), Northern Hemisphere ice conditions (Chiang et al 2003;Chiang and Bitz 2005;Broccoli et al 2006), the Atlantic meridional mode (Nobre and Shukla 1996;Chiang et al 2002;Xie and Carton 2004), and meltwater pulses and AMOC (Broccoli et al 2006;Timmermann et al 2007;Deplazes et al 2013;Marzin et al 2013;Menviel et al 2014). …”
Section: Position Versus Intensitymentioning
confidence: 99%
“…Temporal resolution of this Dansaard-Oeschger (D-O) variability has continually increased (Shackleton et al 2004;Svensson et al 2008) and is now well-established (Rasmussen et al 2014). Completely deciphering the complexity of these events and the mechanisms behind them, however, remains problematic (Broecker 2006;Marcott et al 2011;Menviel et al 2014;Roche et al 2014;Wolff et al 2010). Detailed analyses of marine and terrestrial climatic archives, along with paleoclimatic simulation methods, have allowed for detailed reconstructions of climatic and environmental conditions across Europe during the Last Glacial (Fletcher et al 2010;Kageyama et al 2013;Haibin et al 2007).…”
Section: Introductionmentioning
confidence: 98%